Giant non-linear absorption in Er3+-doped fluoroindate glass - Araújo, Cid B. de; Maciel, G. S.; Rakov, N.; Messaddeq, Younes [UNESP] (Elsevier, 1999)
Non-linear absorption is observed in Er3+-doped fluoroindate glass (in mol% 37InF2:20ZnF2:20SrF2:16BaF2:2GdF2: 2NaF:1GaF3:2ErF3) when the sample is irradiated with a CW laser emitting at 650 nm. An intensity dependence of the optical transmittance is detected. Saturation and sequential absorption of two photons are responsible for the decrease of 50% in the transmittance. The results are explained by simple models which are solved based on rate-equations for the populations of energy levels.
Keywords: Absorption spectroscopy; Continuous wave lasers; Doping (additives); Dye lasers; Erbium; Fluorine compounds; Laser beams; Light absorption; Multiphoton processes; Nonlinear optics; Fluoroindate glass; Nonlinear absorption; Optical glass